Experimental and Numerical Study of Snuber in Hydrogen Compressor - M. Shiddiqur Rahman (Chemical Engineering Diponegoro University, 2012)
In hydrogen production, transportation and delivery system, compression is one of the most important issues. There develop inherently pressure pulsation in reciprocating hydrogen compressing system. An experiment has been conducted to investigate the performance of snubber as pulsation damper used in reciprocating compression system. CFD analysis is applied to get the pressure values at different parts of this snubber. Regression equations are also developed for amplitude at input and output of the snubber. A comparative study of pressure and amplitude by experiment, regression equation and CFD model are performed for 35, 40 and 45 Hz motor frequency. These models results are varied by 3.975%, 3.516% and 3.787% from the experiment for those motor frequencies. The pressure losses in the snubber are also found almost similar values by the regression equation i.e. 0.026%, 0.033% and 0.018% deviations.